2021
DOI: 10.1021/acsanm.0c03046
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Coated Cu2O Nanoparticle Substrates for Surface Azide–Alkyne Cycloaddition

Abstract: Heterogeneous copper nanoparticles (CuNPs) have emerged as a promising alternative to complete the Cu(I)-catalyzed azide−alkyne cycloaddition (CuAAC) owing to better stability and biocompatibility and provide opportunities for surface functionalization of biomolecules. Herein, we fabricated Ag-coated cuprous oxide (Cu 2 O) NP slides to promote dual functions: the metal-enhanced fluorescence effect and external copper ionfree CuAAC reaction. The Cu 2 O NPs were in situ generated on a Ag-coated glass slide, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…BAs only bind weakly to glycans at neutral pH, and their dissociation constant ( K D ) are in the order of 200–10 5 μM range [26] . However, a K D value of 2.68±0.33 μM (Figure S19) was obtained from Her‐Ab (0–6.6 μM) microarrays fabricated on a BA‐functionalized silver‐coated Cu 2 O nanoparticle glass slide, a surface recently reported for signal enhancement [41] . Notably, no apparent detectable binding was observed for deglycosylated Her‐Ab.…”
Section: Resultsmentioning
confidence: 88%
“…BAs only bind weakly to glycans at neutral pH, and their dissociation constant ( K D ) are in the order of 200–10 5 μM range [26] . However, a K D value of 2.68±0.33 μM (Figure S19) was obtained from Her‐Ab (0–6.6 μM) microarrays fabricated on a BA‐functionalized silver‐coated Cu 2 O nanoparticle glass slide, a surface recently reported for signal enhancement [41] . Notably, no apparent detectable binding was observed for deglycosylated Her‐Ab.…”
Section: Resultsmentioning
confidence: 88%
“…We invoked the mechanism based on the following considerations. (i) Much like CuO, it has been shown in several reports that Cu 2 O is also capable of catalyzing the click synthesis. (ii) However, our optimization studies using Cu 2 O (Table , entry 10) have resulted only in trace amounts of the product. Incidentally, Michaud et al also observed the lack of catalytic activity for Cu 2 O toward click chemistry .…”
Section: Resultsmentioning
confidence: 95%
“…Notably, the cleavage of the labeled protein was not quantitative, as evidenced by the appearance of a faint biotinylated protein band in the corresponding immunoblot image (Lane 3). Notably, because of a considerably high affinity ( K D = 31 nM) between GD3 ligand and rSiglec‐7, [ 29 ] a residual labeled protein was still retained on SBs after the cleavage step (Lane 3, SDS‐PAGE vs. Western blotting). However, no further attempt was made to improve the yield of the cleavage step.…”
Section: Resultsmentioning
confidence: 99%
“…Given these results, whether the conjugation of a therapeutic payload molecule to rSiglec‐7 would alter the affinity to bind with the natural glycan ligand was determined. Therefore, a GD3 glycan microarray was fabricated, [ 29 ] and the binding affinity of rSiglec‐7 with alkynylated rSiglec‐7 and 3 ‐rSiglec‐7 was compared (Figure 6c). According to fluorescence intensity measurements, alkynylated rSiglec‐7 and 3 ‐rSiglec‐7 exhibited an affinity for GD3 glycan similar to that of original rSiglec‐7, indicating that the modification of rSiglec‐7 does not affect the original binding activity.…”
Section: Resultsmentioning
confidence: 99%